The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.sleep.2015.02.163
|View full text |Cite
|
Sign up to set email alerts
|

Trauma associated sleep disorder: A proposed parasomnia encompassing disruptive nocturnal behaviors, nightmares and REM without atonia in trauma survivors

Abstract: Study Objectives: To characterize the clinical, polysomnographic and treatment responses of patients with disruptive nocturnal behaviors (DNB) and nightmares following traumatic experiences. Methods: A case series of four young male, active duty U.S. Army Soldiers who presented with DNB and trauma related nightmares. Patients underwent a clinical evaluation in a sleep medicine clinic, attended overnight polysomnogram (PSG) and received treatment. We report pertinent clinical and PSG fi ndings from our patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…When these patients sleep in the monitored sleep laboratory environment that they may perceive as safe, this decreases their usual state of nocturnal hyperarousal, which could translate to more efficient sleep. 51 Further support for this theory is that patients with nightmares rarely have this parasomnia captured during an attended in-laboratory PSG. In terms of the evaluation of NDO and TRN, future studies should consider home PSG with video monitoring where these parasomnias are more likely to occur.…”
Section: Discussionmentioning
confidence: 95%
“…When these patients sleep in the monitored sleep laboratory environment that they may perceive as safe, this decreases their usual state of nocturnal hyperarousal, which could translate to more efficient sleep. 51 Further support for this theory is that patients with nightmares rarely have this parasomnia captured during an attended in-laboratory PSG. In terms of the evaluation of NDO and TRN, future studies should consider home PSG with video monitoring where these parasomnias are more likely to occur.…”
Section: Discussionmentioning
confidence: 95%
“…6 In fact, based on their review of the literature on polysomnographic and self-reported findings among trauma survivors, Mysliwiec and colleagues recently proposed a new parasomnia disorder, "Trauma Associated Sleep Disorder," that is characterized by this commonly reported/observed cluster of symptoms among trauma survivors. 9 Sleep disturbance is a common complaint among those suffering from both acute and chronic mood disorders as well. 10 Approximately 17% of veterans using VA services are diagnosed with depression, 4 and in light of the comorbidity between insomnia and mood disorders, 11 a significant portion of these veterans are likely to have a comorbid insomnia as well.…”
Section: S C I E N T I F I C I N V E S T I G At I O N Smentioning
confidence: 99%
“…DNB following traumatic experiences consists of a constellation of nocturnal symptoms including abnormal behavior or movements or vocalization during sleep associated with autonomic hyperarousal. 12 Importantly, while most studies have queried facets of refugee health in border countries, no study has assessed refugees' sleep quality resettled in the United States. This is important as it examines the unique effects of living difficulties related to resettling in a host country of greater distance, cultural, and geographic distinction from the country of origin.…”
Section: Introductionmentioning
confidence: 99%